A Naturalistic Theodicy for Sterba's Problem of Natural Evil - Moore, Dwayne (Sophia, 2024)
In a series of writings, James Sterba introduces several novel arguments from evil against the existence of God (Sterba, 2019; Sterba Sophia 59, 501-512, 2020; Sterba International Journal for Philosophy of Religion 87, 203-208, 2020b; Sterba International Journal for Philosophy of Religion 87, 223-228, 2020c; Sterba Religions 12, 536, 2021). According to one of these arguments, the problem of natural evil, God must necessarily prevent the horrendous evil consequences of natural evil such as diseases and hurricanes; however, these horrendous evil consequences of natural evils still occur, so God does not exist. In this paper, I reply to Sterba's argument from natural evil by introducing a naturalistic theodicy, and then demonstrating how it overcomes Sterba's problem of natural evil.This paper is divided into five sections. First, I unpack Sterba's problem of natural evil into three parts (Section 1), namely, Sterba's moral obligation claim about humans, Sterba's moral obligation claim about non-human life, and Sterba's arguments from analogy. I then introduce a general naturalistic theodicy to the problem of natural evil (Section 2): naturalists grant that natural forces (entropy, evolutionary pressures, tectonic plate movements, etc.) cause horrendous consequences of natural evil, yet still consider human life in the universe a good better than humans are entitled to, so, if God made this naturalistic universe, God made human life in the universe a good better than humans are entitled to. I then use this naturalistic theodicy to reply to Sterba's moral obligation claim about humans (Section 3), before bolstering the case by appeal to Sterba's moral obligation claims about non-human life (Section 4). I then reply to Sterba's arguments from analogy (Section 5).